DECONSTRUCTION OF THE MAIN CHARACTER IN OSCAR WILDE NOVEL THE PICTURE OF DORIAN GRAY - Sonya, Anna Maria Felicita; Hellystia, Devi (UG Journal, 2021)
Deconstruction does not mean "demolition;" instead it means "breaking down" or analyzing something (especially the words in a work of fiction or nonfiction) to discover its true significance, which is supposedly rarely exactly what the author intended. This research aims at finding out the form of deconstruction character that is found in the novel The Picture of Dorian Gray by Oscar Wilde. The data were taken from dialogue, sentences, and passages from the novel. It is qualitative research in which the data were elaborated descriptively by using deconstruction theory by Jacques Derrida as a tool to analyze the character. The result of the research shows that there are indications of other traits that exist in the main character, Dorian Gray, before being deconstructed Dorian Gray character was a cruel, cold -hearted, and mean person, and after being deconstructed it proved that Dorian Gray also has character merciful, softhearted and kind person. This research implies that from the other traits found in the main character there is a possibility that it will not appear completely.